2023
DOI: 10.1038/s41598-023-36119-y
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-physiological responses and growth indices of triticale to drought and salt stresses

Abstract: Salinity and drought are two major abiotic stresses challenging global crop production and food security. In this study, the effects of individual and combined effects of drought (at different phenological stages) and salt stresses on growth, morphology, and physiology of triticale were evaluated. For this purpose, a 3 x 4 factorial design in three blocks experiment was conducted. The stress treatments included three levels of salinity (0, 50, and 100 mM NaCl) and four levels of drought (regular irrigation as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The decrease in Spad could have stemmed from drought-damaged leaves turning yellowish. Drought stress has been shown to reduce chlorophyll content in wheat ( Talebi, 2011 ), triticale ( Mohammadi Alagoz et al., 2023 ), maize ( Mohammadkhani and Heidari, 2007 ), chickpea ( Mafakheri et al., 2010 ), soybean ( Makbul et al., 2011 ), and rice ( Jnandabhiram and Sailen Prasad, 2012 ). The reduction in Spad is due to chloroplast damage stemming from active oxygen species ( Golldack et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in Spad could have stemmed from drought-damaged leaves turning yellowish. Drought stress has been shown to reduce chlorophyll content in wheat ( Talebi, 2011 ), triticale ( Mohammadi Alagoz et al., 2023 ), maize ( Mohammadkhani and Heidari, 2007 ), chickpea ( Mafakheri et al., 2010 ), soybean ( Makbul et al., 2011 ), and rice ( Jnandabhiram and Sailen Prasad, 2012 ). The reduction in Spad is due to chloroplast damage stemming from active oxygen species ( Golldack et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The proline content was measured by ninhydrin staining of Shen et al [18] and calculated using a proline standard curve (0-50 mg•mL −1 ) identically. A previous method was used for the determination of photosynthetic pigments (total chlorophyll, chlorophyll a and chlorophyll b), and total chlorophyll was calculated as chlorophyll a + chlorophyll b [19]. The absorbance of the extract was measured at 470, 663 and 645 nm using a spectrophotometer (TU-1810, Puxi General Instrument Co., Ltd., Beijing, China).…”
Section: Determination Of Physiological Indicatorsmentioning
confidence: 99%
“…Producing high-quality and high-yield crops is not only a concern for farmers but also a popular topic among researchers. Crops accumulate both inorganic and organic solutes and change their physiological function to cope with environmental stresses, which leads to changes in yield and quality (Alagoz et al, 2023). Wang et al (2017) demonstrated that in the southern arid region of Xinjiang, the use of brackish water with a salinity ranging from 2.36 to 3.39 g•L − 1 for mixed irrigation had minimal impacts on cotton growth and yield and irrigation water use e ciency.…”
Section: Introductionmentioning
confidence: 99%